Secular trends in blood pressure in children: A systematic review - Roulet, Céline (J Clin Hypertens (Greenwich), 2016)
Blood pressure (BP) is expected to have increased over time in children in most countries due to the increasing prevalence of childhood obesity worldwide. The authors conducted a systematic review of studies assessing secular trends in BP in children and adolescents. Of 1739 citations screened, the authors identified 18 studies including 2 042 470 participants examined between 1963 and 2012. Thirteen studies were conducted in high‐income countries, five in middle‐income countries, and none in low‐income countries. The prevalence of overweight or obesity increased in 17 studies and decreased in one study. BP decreased over time in 13 studies, increased in four, and did not change in one. These findings suggest that secular trends in BP do not mirror secular trends in overweight. This implies that other factors mitigate the effect of overweight on BP in children and adolescents.